Quality Processes in the Teaching of Reading: The Origin of a Democratic and Participatory Knowledge - Fernando Rodríguez-Valls (Universidad Autónoma de Madrid, 2016)
On the last decade, state test scores obtained by adolescent students grades eight through twelve have defined the quality processes of educational programs in public schools in the United States. One consequence of this dynamic is the trend by school districts to implement reading programs for adolescents that focus almost exclusively on teaching "reading to pass the exam." Within this framework, promoting educational processes that ensure the development of reading as a rewarding activity that enriches the experiences of adolescents has become a challenge for teachers. This article analyzes a study conducted to capture and echo the ideas and suggestions in the area of reading-related activities of fifty Latino students attending high schools in the Imperial Valley, California. The aim was to build a database, and display it on a web page, that reflected the students' proposals on how to improve the quality of the programs designed and developed by commercial book companies and approved by the California Department of Education. Listening to the questions and ideas shared by these students, set out in individual interviews and group discussions, serves as wake-up call for administrators and academic counselors. The core of the students' reflections indicate that the quality process of the current functional reading practices-read to respond and to pass the exam-must be expanded and enriched with activities that explicitly teach the student how to read critically. Students participating in this study, aware that any change requires their dedication, commit themselves to increase their participation on the quality of the learning process. To accomplish the latter, they ask for a participatory methodology of reading where students and teachers cooperatively build knowledge.